Engaging e-Learning in Higher Education: An Empirical Student Engagement Model for LMS-Mediated e-Tutorials - Kigundu, Stephen (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
This study focused on developing an empirical student engagement model tailored to LMS-mediated higher education tutorials. As part of a larger initiative to create innovative learning strategies for first-year students. The research aimed to bridge the gap between prior knowledge and higher education demands using LMS-mediated tutorials. Despite the widespread adoption of Learning Management Systems (LMS) in delivering online tutorials, student engagement remains a significant challenge. In this article, which uses parts of the author’s doctoral study, developing a Trigonometry module consisting of course content in the form of resources and tasks was used to identify key determinants of student engagement in LMS-mediated e-tutorials. A mixed-method research approach with a reflexive self-study research design was used. 129 first-year university student volunteers were used to test the tutorial through 4 development cycles. Through an empirical qualitative approach, questionnaires, interviews, direct observations, screen capture videos and student work samples were used as data collection methods. The research highlights critical issues in current e-tutorial designs and proposes actionable improvements. The findings underscore the importance of addressing both cognitive and behavioural engagement strategies to enhance e-learning experiences and outcomes. This research offers valuable insights for educators and institutions seeking to foster deeper student engagement and improve the effectiveness of e-learning environments.